VAT in Haryana - Mukhopadhyay, Sukumar (2005)
Revenue growth is the most important aspect by which to judge the success of VAT in Haryana. The deemed growth of revenue estimated by the Commercial Tax Department of Haryana, however, has not taken into account a number of positive factors discussed in this paper. As Haryana implemented VAT only in 2003, one year is too short a period to judge its efficiency from a revenue point of view. - Reproduced.
Keywords: Taxation - India - Haryana; Taxation